Does Green Supply Chain Management Improve Sustainable Performance? - Rizki, Adam Firman; Murwaningsari, Etty; Sudibyo, Yvonne Augustine (International Journal of Energy Economics and Policy, 2022)
The process of Green Supply Chain Management (GSCM) is widely associated with its contribution to the company's sustainability performance. The GSCM process will also be linked to an integrated system of Enterprise Resource Planning (ERP) that affects the achievement of sustainability performance. The importance of environmental consciousness from producers to direct their business processes that are beneficial to the environment in the long term. This study used 507 samples of manufacturing companies in Indonesia. Data was obtained by giving questionnaires to middle-up managers in departments related to the GSCM process. GSCM and ERP affect the Company's Sustainability Performance. Moderation of environmental consciousness strengthens the influence of GSCM on sustainability performance. GSCM, ERP, and environmental consciousness simultaneously affects sustainability performance by 90.3%. This research provides a new measurement in the form of 5 indicators in the GSCM and 5 indicators for sustainability performance. In this research doesn’t discuss about explain bottleneck and risk in GSCM implementation such as regulation about logistic and distribution. This paper can be a guide for practitioners in the supply chain field to use GSCM measurement indicators to be applied in companies, which aim to achieve sustainable performance.